Evaluating the Influence of Intermittent Weather Condition on the Effectiveness of Solar Photovoltaic System: The Case of Ntyuka Transmission Station (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
Conventional fossil-based power generation has increased global electrical output but introduced environmental stress, cost volatility, and resource depletion. Solar photovoltaic (PV) systems offer a feasible low-emission option; however, their efficacy is intrinsically affected by nonlinear factors associated with solar irradiance and module temperature, rendering weather variability a significant operational limitation. This study assesses the impact of intermittent weather conditions on the performance of the standalone 6 kW PV system at Ntyuka Transmission Station in Tanzania. Measured site parameters—including hourly global horizontal irradiance, module surface temperature, system component specifications, and recorded AC output power—were incorporated into a MATLAB/Simulink model representing the PV array and inverter configuration. Model validation was performed by comparing simulated system behaviour against measured operational data under varying environmental scenarios. Results indicate that fluctuations in irradiance from 1200 W/m² to 700 W/m² lead to significant voltage and power reductions, contributing to an average energy loss of 18–22%. The study confirms that intermittency reduces system efficiency, output stability, and supply reliability. The findings highlight the need for improved system control strategies, optimised sizing, and supportive policy measures to enhance the technical viability of off-grid PV systems in Tanzania.